ดนตรีพระราชพิธีสิบสองเดือนตามวาระที่ปรากฏในปฏิทินหลวง Royal Ceremonial Music for Monthly Celebrations according to Royal Calendar - คมขำ, ภัทระ (Journal of Fine and Applied Arts Khon Kaen University, 2015)
งานวิจัยเรื่องดนตรีในพระราชพิธีสิบสองเดือนตามวาระที่ปรากฏในปฏิทินหลวง ทุนวิจัยเฉลิมฉลองสมเด็จพระเทพรัตนราชสุดา ฯ สยามบรมราชกุมารี จุฬาลงกรณ์มหาวิทยาลัย มีวัตถุประสงค์เพื่อศึกษาความเป็นมา ระเบียบวิธีการบรรเลง องค์ประกอบของวงดนตรีและบทเพลง โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพ ผลการวิจัยพบว่า เดิมพระราชพิธีจำแนกได้ 3 ประเภทคือพระราชพิธีที่เกี่ยวข้องกับศาสนาพราหมณ์พระพุทธศาสนาและความเชื่อโบราณ สำหรับปฏิทินหลวง ปี พ.ศ. 2557 ปรากฏ 41 พระราชพิธี/รัฐพิธี วงเครื่องประโคมปรากฏ 2 วงได้แก่วงพระสวาเคิ่น 1 ประกอบด้วยแตรฝรั่งและกลองมโหระทึก และวงพระสวาเคิ่น 2 ประกอบด้วยฆ้องชัย สังข์ แตรฝรั่ง แตรงอน ทั้ง 2 วงปรากฏบทเพลงที่ใช้อยู่ปัจจุบันได้แก่เพลงสำหรับบท เพลงออกขุนนางและเพลงส่งเสด็จ บทเพลงที่ใช้เป็นหลักในวงปี่พาทย์ที่ใช้ในงานพระราชพิธีได้แก่เพลงช้า เพลงสาธุการและเพลงกราวรำ นอกจากนี้ยังปรากฏเพลงลงสรง เพลงกราวรำ ชั้นเดียวและเพลงเรื่องเวียนเทียนด้วย สำนวนเพลงมีการฉายมือ ปรากฏทั้ง “สองชั้นฉาย” และ “ชั้นเดียวฉาย” การจัดแบ่งหน้าที่ของผู้ปฏิบัติงานวงเครื่องประโคมแบ่งเป็น 4 วง สำหรับวงปี่พาทย์พระราชพิธีแบ่งออกเป็น 5 วง การปฏิบัติหน้าที่ของนักปี่พาทย์แต่ละวงจะบรรเลงงานพระราชพิธีและงานอื่นๆ ตามที่ได้รับมอบหมายด้วย A research on the music performed during the Royal Ceremonies of the Twelve Months at various times of the year as indicated in the royal calendar. Princess Maha Chakri Sirindhorn Celebrations research grant, Chulalongkorn University. Research objectives: To study the origin and performing techniques of this type of music as well as the components of the relating musical ensemble and songs. Qualitative research methodology is employed in this research. The research findings revealed that there were initially three categories of the royal ceremonies: those related to the Brahmin, Buddhist, and ancient beliefs. There is a total of 41 royal/state ceremonies in the 2014 royal calendar. Two Khrueng Prakom ensembles perform at these ceremonies: Phra Swakern 1, which consists of trumpets and kettle or Maho-ra therk drums; and Phra Swakern 2, which consists of Khaw-ng Chai, conches, trumpets, and old Thai horns. The current songs performed by both musical ensembles during the royal ceremonies are phleng samrap bot, phleng ok khunnang, and phleng song sadet. The principal songs performed by phiphat ensembles for the royal ceremonies include phleng cha, phleng sadhukarn, and phleng krao rum. Other songs are phleng long song, phleng krao rum chan diew, and phleng rueng wien thien. “Song Chan Chai” and “Chan Diew Chai” hand movement techniques are used in the performance. Musicians in Khrueng Prakom ensembles divide their performance duties to 4 groups. There are five phiphat ensembles performing at royal ceremonies and the musicians of each ensemble perform at royal ceremonies as well as at any other functions assigned to them.